2020
DOI: 10.1523/jneurosci.0370-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Divergent Medial Amygdala Pathways Drives Experience-Dependent Aggression Escalation

Abstract: Heightened aggression can be serious concerns for the individual and society at large and are symptoms of many psychiatric illnesses, such as post-traumatic stress disorder. The circuit and synaptic mechanisms underlying experience-induced aggression increase, however, are poorly understood. Here we find that prior attack experience leading to an increase in aggressive behavior, known as aggression priming, activates neurons within the posterior ventral segment of the medial amygdala (MeApv). Optogenetic stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(110 citation statements)
references
References 109 publications
(167 reference statements)
7
102
1
Order By: Relevance
“…MeApv have different effects on aggression (Kollack-Walker and Newman, 1995;Lin et al, 2011;Hong et al, 2014;Miller et al, 2019;Nordman et al, 2020b), it is worth considering that the DR may be shortening an attack through a specific subregion of the MeA. The photostimulation protocol used in this study does not allow for discrimination of these subregions due to their anatomical clustering.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MeApv have different effects on aggression (Kollack-Walker and Newman, 1995;Lin et al, 2011;Hong et al, 2014;Miller et al, 2019;Nordman et al, 2020b), it is worth considering that the DR may be shortening an attack through a specific subregion of the MeA. The photostimulation protocol used in this study does not allow for discrimination of these subregions due to their anatomical clustering.…”
Section: Discussionmentioning
confidence: 99%
“…The three main MeA subregions, MeAa, MeApd, and MeApv, are all involved in aggressive behavior (Kollack-Walker and Newman, 1995;Lin et al, 2011;Hong et al, 2014;Miller et al, 2019;Nordman et al, 2020b). While we observed that photostimulation of the DR can activate all three subregions, since the MeApd and…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VMHvl Esr1 neurons receive inputs from neurons in over 30 different structures (50), raising the question of whether other inputs to these cells also display plasticity. Indeed, recently published work has identified synaptic plasticity promoted by foot-shock stress in a medial amygdala projection that primarily targets the central part of VMH (VMHc) (127). Although a causal role in promoting aggression was not directly demonstrated for this input, and the mechanism of potentiation was not established, plasticity at this synapse may regulate stress-induced aggression (127).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently published work has identified synaptic plasticity promoted by foot-shock stress in a medial amygdala projection that primarily targets the central part of VMH (VMHc) (127). Although a causal role in promoting aggression was not directly demonstrated for this input, and the mechanism of potentiation was not established, plasticity at this synapse may regulate stress-induced aggression (127). The present study demonstrates that AHiPM VMHvl Esr1 synapses can undergo Hebbian LTP, and that potentiation of these synapses occurs during social experience that enhances offensive aggression (47,119).…”
Section: Discussionmentioning
confidence: 99%